The Study of Mono- and Polysubstance Abuse Effects on Complete Blood Count Parameters in Samples of Iraqi Patients - Athmar Kadhim Gatea; Kareem Nasir Hussien; Mohammed Ali Al-Jabory (Journal of Applied Hematology, 2024)
BACKGROUND: Substance abuse represents a major health problem worldwide. In Iraq, the number of substance abusers increased, both single and polysubstance, alcohol and medications. Abuse of these substances is associated with changes in different blood parameters secondary to their direct immune, inflammatory, toxic and stressor effects on hematopoiesis, and indirect effect on liver and kidneys. These changes involve total white blood cell (WBC) count, especially lymphocyte count and their ratio to neutrophil count and platelet (PLT), in addition to their effect on red blood cell (RBC) and PLT parameters, and pancytopenia. OBJECTIVES: We evaluated the effect of substance abuse on the complete blood count (CBC) parameters. PATIENTS AND METHODS: This study was performed over 6 months on 114 participants; 57 of them were substance abusers and 57 were healthy people from Al-Sadiq Teaching Hospital/Psychiatry Department. A questionnaire was used to collect the demographic data related to substance including type, number and duration of abuse. In addition a blood sample was collected from the participants for CBC assessment. RESULTS: There is a significant difference between substance abusers and healthy people in WBC parameters only in lymphocyte count (P = 0.004) and neutrophil/lymphocyte ratio (P = 0.03). In RBC parameters, RBC count (P = 0.005), mean corpuscular volume (P = 0.008), mean corpuscular hemoglobin (P = 0.04), and red cell distribution width-standard deviation (P = <0.0001). In PLT parameters, PLT count (P = 0.007), mean PLT count (P = <0.0001), PLT-large cell ratio (P = <0.0001), and PLT/lymphocyte ratio (P = 0.0006). For the duration of substance abuse as well as the number of substance abuse, the only significant change in the CBC was involving the lymphocyte count (P = 0.04). CONCLUSION: Polysubstance misuse is widespread in samples taken and has a significant effect on different hematological parameters. This finding is correlated with different studies worldwide increasing the need for attention payment in the follow-up and management of drug addicts.